Decision analysis on disposal of large quantities of excavated soft soil in abandoned mines using a Bayesian network. Issue 6 (3rd July 2022) - Wu, Linbo; Zhan, Liangtong; Zhang, Shuai; Song, Xue; Lu, Junyao; Wang, Yong
ABSTRACT: Disposal of the excess excavated soft soils produced in construction is a contemporary engineering challenge. A win-win solution could be found through utilising much excavated soil during reclamation of abandoned mines, and an evaluation model is necessary to realise this solution. This study aimed to propose a decision-making framework for large-scale disposal of excavated soft soil during mine reclamation using a Bayesian network (BN). Utilising multi-facet information, a decision-making path considering engineering and economic factors, and engineering risks was established. Thereafter, the practicability of backfilling much excavated soft soil into 215 abandoned opencast mines located in Wenzhou, China was evaluated. Based on the decision-making path and information of the 215 mines, a BN including 22 nodes was established with the practicability of large-scale soil disposal in mines as the decision node. Consequently, 40 valid mines were evaluated to be able to absorb 5 × 10 7  m 3 soil, around 50% of the total excavated soil from the municipal districts of Wenzhou during 2020–2024. The BN evaluation showed high reliability with accuracy of all the nodes >70% and that of the decision node >90%. Five input nodes were identified to be high-impact for evaluation of the practicability and total fill volume.